Hubungan Sikap Dan Pengetahuan Ibu Menyusui Dengan Pemberian Asi Eksklusif Pada Bayi UPTD Puskesmas Sultan Daulat Kabupaten Subulussalam Tahun 2023 - Trinovika Futri Dewi; Yasrida Nadeak (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2024)
According to the Nort Sumatera Provincial Health Service, exclusive breastfeeding is given to babies 0-6 months were 20,394 with a percentage of 67%. This is experienced a decrease in 2018 in the percentage of exclusive breastfeeding in the province Nort Sumatera as much as 76%. This research aims to determine the relationship knowledge and attitudes of breastfeeding mothers towards exclusive breastfeeding in working area of ​​the Sultan Daulat Health Care Center, Sublussalam City in 2023.This research uses a population cross-sectional research method in this study were all mothers who had children aged 6-24 months which is in the Working Area of ​​the Sultan Daulat Health Center, Sublussalam City totaling 274 people. The sample in this study was 56 respondents with purposive sampling technique. This research instrument uses questionnaire. Analyze data using univariate, bivariate, multivariate.The conclusion from this research is that there is a relationship between mother's knowledge towards exclusive breastfeeding there is a relationship between age and exclusive breastfeeding. There is the most dominant factor in exclusive breastfeeding is age. It is hoped that health services should provide in-depth information increase exclusive breastfeeding.